Modeling of socio-psycho-organizational variables from the state of the art (Revista de la Facultad de Trabajo Social, 2020)
Sociological and psychological studies have developed explanatory models of the relationship among organizational variable; using such models as a starting point, this paper reviewed studies corresponding to the decade in order to discuss the findings and specify two models: one concerning perceptual determinants and the other regarding the socioeconomic determinants of job satisfaction. Both models Will contribute to the discusión on the relationship among psychological, socioeconomic and situational variables as determinants of job satisfaction.
Keywords: climate; stress; confideace; commitment; performance; leadership; satisfaction